Expansion of telehealth curriculum: National survey of clinical education leaders. (July 2022) - Jortberg, Bonnie T; Beck Dallaghan, Gary L; Schatte, Dawnelle; Christner, Jennifer; Ryan, Michael S
Introduction: In response to the COVID pandemic and the rapid changes in delivery of and education on telehealth services, the Research Committee of the Alliance of Clinical Education (ACE) surveyed its multidisciplinary group of medical educators to determine how telehealth was being taught pre-COVID versus during-COVID. Methods: An online survey was developed by the ACE Research Committee and sent via email to the ACE delegation. The objective of the survey was to determine changes in telehealth curriculum for medical students due to the rapid transition to telehealth, and the barriers for developing and delivering a telehealth curriculum. Results: Forty-nine percent of recipients (31/63) responded representing eight different disciplines in addition to institutional curriculum developers. Most programs had no formal didactics and no clinical experiences in telehealth prior to the pandemic. Most respondents added didactics and clinical telehealth encounters during COVID, although few schools required this of all students. Discussion: Given the barriers of faculty training to pivot to telehealth, and the potential benefits to healthcare cost and patient satisfaction, there is a need for more formal study on best practices for teaching telehealth to prepare our future physicians.